2003
DOI: 10.1016/s0194-5998(03)00454-6
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety in the first attack of vertigo

Abstract: Patients with acute vertigo experience extreme anxiety, and this contributes to their feeling of disproportionate disability. The reason for emotional disturbances in vestibular dysfunction is probably the result of physiological connections between the vestibular and limbic system and deserves further neuroanatomic investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 24 publications
2
42
1
3
Order By: Relevance
“…Recent papers have focused on increasing evidence for a possible overlap between psychiatric and vestibular disorders, BPPV among them, and among patients presenting dizziness, psychiatric disorders are elevated to 5-15 times the rate of the general population [28]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent papers have focused on increasing evidence for a possible overlap between psychiatric and vestibular disorders, BPPV among them, and among patients presenting dizziness, psychiatric disorders are elevated to 5-15 times the rate of the general population [28]. …”
Section: Discussionmentioning
confidence: 99%
“…Overlapping neural circuits between anxiety and the balance control system may provoke increased anxiety levels in subjects after an acute vertigo episode, and subjects developing higher anxiety have an incomplete central adaptation [20,21,22,23,24,25,26,27,28,29]. …”
Section: Discussionmentioning
confidence: 99%
“…In Ménière disease, attacks of vertigo have been described as terrifying, resulting in feelings of helplessness and powerlessness (Yardley, 1997). The first attack in particular may be perceived as life threatening, as people do not know what is happening to them (Pollak et al, 2003;Yardley, 1997). Symptoms of PTSD such as avoidance behavior and increased levels of arousal have been reported among people with vestibular disorders (Cohen et al, 1995;Jacob et al, 2002;Yardley et al, 1998).…”
mentioning
confidence: 99%
“…When total slow phase velocity was less than 20 o / second, stimulations were considered hyporesponsive, and hyper-responsive when greater than 140 o /second 11,12 . We considered central signs to comprise at least one of the following findings: [1] disorganized pursuit and reduction of pursuit gain; [2] saccades dysmetria with undershoot, overshoot, or asymmetrical latency or velocity; [3] rebound nystagmus; [4] visual fixation suppression of nystagmus of less than 60 per cent; [5] pure vertical or torsional spontaneous or positional nystagmus; or [6] positional nystagmus when bilateral, beating to the uppermost or lowermost ear, showing no latency, low frequency, lack of fatigability and habituation, without concomitant vertigo 14,15 . The otoneurological evaluations were conducted before the initiation of treatment with imipramine, and were repeated after three months of treatment with imipramine.…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of rotational vertigo, dizziness has been considered another somatoform symptom common to anxiety disorders 1 . Psychiatric disorders have been associated with chronic dizziness in the so-called idiopathic dizziness 2 , and different studies have shown that patients that suffer from acute vestibular conditions often develop psychiatric disorders 3,4 . Patients with anxiety disorders have a higher rate of peripheral vestibular dysfunction compared to control populations, especially in panic disorder with agoraphobia 5 .…”
mentioning
confidence: 99%